Marvelous Marine Microgels: On the Distribution and Impact of Gel-Like Particles in the Oceanic Water-Column - Engel, Anja; Endres, Sonja; Galgani, Luisa; Schartau, Markus (Frontiers in Marine Science, 2020)
Three-dimensional hydrogels of organic polymers have been suggested to affect a variety of processes in the ocean, including element cycling, microbial ecology, food-web dynamics, and air-sea exchange. However, their abundance and distribution in the ocean are hardly known, strongly limiting an assessment of their global significance. As a consequence, marine gels are often disregarded in biogeochemical or ecosystem models. Here, we demonstrate the widespread abundance of microgels in the ocean, from the surface to the deep sea. We exhibit size spectra of two major classes of marine gels, transparent exopolymer particles (TEP) and Coomassie stainable particles (CSP) for three different ocean regimes: a) polar seas, b) eastern upwelling systems and c) the oligotrophic open ocean. We show the variations of TEP and CSP over the water-column, and compare them to dissolved organic carbon (DOC). We also discuss how the observed distributional patterns give potential insight to the productivity and particle dynamics of these distinct oceanic regimes. Finally, we exploit current research topics, where consideration of microgels may give new insight into the role of organic matter for marine biogeochemical processes.